Analogy and explicit motor learning in dynamic balance: Posturography and performance analyses - Kim, S.-M.; Qu, F.; Lam, W.-K. (European Journal of Sport Science, 2021)
Unlike explicit learning, analogy learning allows learners to acquire skills with a movement metaphor with fewer verbal knowledge accumulated during early learning, resulting in less reliance on cognitive resources for better motor performances. However, the efficacy of analogical instruction on balance is still unclear. This study examined learning and subsequent performance (including posturography) of a Y-balance task by explicit and analogical instructions. Forty female undergraduates were randomly assigned either into analogy (n = 20) or explicit (n = 20) learning. Both group learners completed pre-learning test-block on Day 1 (6 trials), five consecutive learning blocks from Days 3 to 7 (135 trials) and followed by test-blocks on Day 9 (retention 1 - dual-task - retention 2 design, 18 trials). Maximum reaching distances in anterior, posterolateral and posteromedial directions were measured to indicate Y-balance performance. During test-blocks (pre-learning, retention 1, dual-task, retention 2), CoM displacement and CoP excursion were quantified with the motion capturing system and force platform, respectively. Results indicated that maximum reach distances of two groups increased across learning days (p < .001). During test-blocks, explicit learners reduced maximum reaching distances under the dual-task test than the retention test 1 (p < .001), while analogy learners remained robust performance across test-blocks (p = .071). Moreover, analogy learners reported fewer explicit knowledge and demonstrated better counting backward performance than explicit learners. These findings suggest that introducing an analogical instruction in dynamic balance training is feasible and has implications to develop balance training strategies for injury prevention and performance enhancement.